From Bytes to Booth: Exploring Privacy Concerns in Voting Advice Applications - Rauti, Sampsa; Heino, Timi; Puhtila, Panu (United States, 2025)
In this study, we conduct a network traffic analysis of Finnish voting advice applications. We analyze the potential third-party data leaks in 8 voting advice applications first during the 2023 parliamentary election and then during the 2024 presidential election. The goal is to study whether sensitive information, such as individuals’ political opinions, leak to third parties. Furthermore, the paper also describes the change in privacy of voting advice applications after the leaks found in 2023 were covered in the media. The findings indicate that media attention and public discourse has had a clear positive impact on the privacy of Finnish voting advice applications, but a few data leaks and privacy concerns still remain. We conclude by discussing how to protect political opinions and democratic processes in increasingly digital society.
CSAE '24: Proceedings of the 8th International Conference on Computer Science and Application Engineering